A case study of an international teaching practicum program in Thailand: Indonesian EFL teacher trainees’ teaching strategies, challenges, and intercultural sensitivity level - Rustandi, Andi; Agusandra, Ayuninda; Sugiarto, Bambang Ruby; Febriani, R. Bunga (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Research on international teaching practicum (ITP) has revealed challenges for teacher trainees, particularly in advancing their teaching strategy in the context of intercultural context. However, other studies suggest that the program holds the potential for the development of teachers trainees’ skills. This study examines the teaching strategies and difficulties encountered by Indonesian EFL teacher trainees and their intercultural sensitivity level during the ITP program in Thailand. This case study involved three Indonesian EFL teacher trainees participating in the ITP program in Thailand. Data were obtained from questionnaires, observation, and interviews. The quantitative data were analyzed statistically, while qualitative data were analyzed thematically. The findings revealed that participants employed a variety of teaching tactics, including goal setting, working examples, noting similarities and differences, providing recognition, assigning homework, providing feedback, practicing, visual scaffolding, modeled discourse, the grammar-translation approach, and facing some cultural barriers. Furthermore, the intercultural sensitivity level demonstrated that all teacher trainees can interact, appreciate differences, be confident, enjoy, be attentive, and value different perspectives when communicating in multicultural circumstances. The study implies that the ITP program should be continued by facilitating a bridging course to cope with intercultural context.